The effect of topical insulin application on the healing of acute tympanic membrane perforations: a histopathologic study - BOZKURT, SÜHEYLA (SPRINGER, 2007)
The aim of the present study was to investigate the effects of insulin on the healing of acute traumatic tympanic membrane (TM) perforations by observing the duration of perforation closure clinically and by examining the TM thickness, fibroblastic reaction, neovascularization and collagenization histologically. In all, 24 adult healthy guinea pigs were used. TM perforations, about 2 mm in diameter were made in the pars tensa of each ear. The perforations in the right ears of the guinea pigs (study group) were treated with 1 IU of regular insulin (Humulin-R-(R) 100 IU/ml, Lilly) daily topically. The left ears of the guinea pigs (control group) were treated with saline solution daily. The treatments were continued until the each perforation closed. The animals were examined with otomicroscopy at first, third, fifth and seventh days. TM specimens were obtained after the animals were decapitated under deep anesthesia by an intraperitoneal injection of sodium pentobarbital (0.5 ml/100 g) 3 and 7 days after wounding. Histologically, the epithelial and mucosal layers were examined. Finger-like projections, the edema of the LP, neovascularization of LP, fibroblastic activity of LP, inflammatory cell presence of LP, collagenization ratios of LP were evaluated. In the study group; LP fibroblastic reaction positivity and LP collagenization positivity was significantly higher than the control group (P < 0.001 and P < 0.05). Topical insulin treatment may be more beneficial in the treatment of atrophic membrane, which is a sequel of perforation, when tried in various dosages and time intervals.
Keywords: topical insulin; myringotomy; wound healing; perforation